Pemodelan Perpindahan Panas (Heat Transfer) Beton Silinder Pada Saat Terbakar - Dyna Aulia R; Alfian Kamaldi; Reni Suryanita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Fire hazard can bring serious problems to reinforced concrete buildings. At combustion temperatures, heat from the fire propagates from the surface into the core of the concrete. This study aims to model the heat transfer on concrete and the results were compared to numerical method proposed by Wickstrom (1987). The specimen used in this study was a concrete cylinder with the diameter of 150 mm and the height of 300 mm. The specimen was exposed to a combustion temperature of 800oC with the combustion duration of 3 hours. The model carried out in the LUSAS v.16 program. Measurements were made at the distance of 19, 38, 56, and 75 mm from the perimeter of cylinder. The results of the study showed the difference in temperature increase using 2D, 3D, and Wickstrom model. For comparison between Wickstrom and 2D at a depth of 19 mm is 15.96%, for 38 mm is 43.57%, for 56 mm is 66.95%, and for a distance is 75 mm of 89.93%. Moreover, the results gained from 2D finite element analysis was 2,05% higher than 3D finite element analysis. The greater the depth of the review, the results between model and Wickstrom method will be much different. The average value of these results can be used as a reference value of the temperature increase at the point of review at a certain distance from perimeter of cylindrical concrete model under high temperatures.Key words: heat transfer, thermal conductivity, specific heat , LUSAS v.16, Wickstrommethod.